Hair follicle melanocyte precursors are awoken by ultraviolet radiation via a cell extrinsic mechanism1. Issue 6 (3rd June 2015) - Ferguson, Blake; Kunisada, Takahiro; Aoki, Hitomi; Handoko, Herlina Y.; Walker, Graeme J.
<x xml:space="preserve">Abstract</x> Melanocyte stem cells in the hair follicle respond to UVR-induced damage by dividing and migrating upwards into the epidermis. This effect is driven by paracrine signals from epidermal keratinocytes induced by adaptive changes in the skin resulting from multiple UVR exposures.